PENGARUH FAKTOR-FAKTOR FUNDAMENTAL PERUSAHAAN, KURS DAN TINGKAT BUNGA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mokhamad Kodir (Universitas Peradaban, 2013)
Researches on the influence of fundamental factors, exchange rate, and interest rate on corporate value have been widely conducted, however results inconsistency occurred. Fundamental factors, exchange rate, interest rate, which in this case is assessed by growth, leverage, profit/Return on Equity (ROE), dividend payout ratio have a positive effect on corporate value; however there are also some findings that, leverage, profit/Return on Equity (ROE), dividend payout ratio have a negative effect. Researchers predicted that there are other influencing factors. This condition drives researchers to use exchange rate, interest rate as adding variables. This research aims to test the influence of fundamental factors on corporate value by adding the two variables.This research uses 10 manufacturing firms listed on the Indonesian Stock Exchange during 2003-2009 as samples with 63 observations. Hypothesis is tested using Pooled Regression Models to find out the interactive influence of the two variables. The corporate value measured using Tobin's Q.Results indicate that (1) ROE has a positive effect on corporate value, (2) growth has a negative effect on corporate value, (3) leverage has a negative effect on corporate value, (4) DPR has a negative effect on corporate value, (5) exchange rate has a negative effect on corporate value, (6) interest rate has a negative effect on corporate value, (7) growth, leverage, profit/Return on Equity (ROE), exchange rate, interest rate affect the corporate value which Tobin’s Q acts as its proxy.